Design and experiment on atomizer parameter of impinging low-speed centrifugal atomization sprayer - Liu, Dejiang; Gong, Yan; Chen, Xiao; Zhang, Xiao; Wang, Guo (International Journal of Agricultural and Biological Engineering, 2020)
Atomizers were designed with different atomization parameters to obtain droplets that satisfy optimal particle size requirements for an impinging-type low-speed centrifugal atomizing sprayer. The main factors affecting droplet size are turntable speed, the number of teeth and the tooth shape of the toothed disc. Winner318 software was used to evaluate droplet sizes for different structures and the working parameters of the atomizer. The response surface method and Design-Expert were used to analyze the effect of each factor. The response surface analysis of the effect of structural and working parameters of the atomizer on the interaction between the volume medium diameter of the droplet and the spectral width of the droplet size was used to establish the atomizer droplet Granular spectrum prediction model. Optimal design fitting formulas are obtained, and the droplet sizes required for pesticides to control flying insect pests, to control the growth of reptile larvae, and the use of spraying fungicides to prevent crop damage were determined. This research provides a product not only similar to those in the market, but also the theoretical basis and references for innovation, development, and optimization of centrifugal atomization technology.Keywords: centrifugal atomization, impinging low-speed, droplets diameter, optimal biological particle size theory, quadratic regression analysisDOI: 10.25165/j.ijabe.20201306.5617Citation: Liu D J, Gong Y, Chen X, Zhang X, Wang G. Design and experiment on atomizer parameter of impinging low-speed centrifugal atomization sprayer. Int J Agric & Biol Eng, 2020; 13(6): 118–124.